The Relationship of Anterior Cruciate Ligament Lesions and Osteochondral Lesions with Meniscal Tears in Patients Younger than Fifty Years of Age - Samed Ordu; Erhan Bayram; Ercan Çetinus; İbrahim Kaya; Murat Yılmaz (Haseki Tıp Bülteni)
Aim: The purpose of this study was to determine the incidence of anterior cruciate ligament (ACL) lesions and osteochondral lesions according to type and localization of the meniscal tear and age, gender in patients who have been arthroscopicaly treated, besides, to make the coexisting lesions more predictable in these patients. Methods: We retrospectively investigated 352 patients under 50 years of age who underwent surgery for a meniscal tear between 2008 and 2012. We scanned the surgical operation notes, preoperative questionnaires and the magnetic resonance imaging findings. We recorded patients who had ACL lesions, such as elongation, partial rupture and total rupture. Osteochondral lesions were classified according to the Outerbridge classification from grade 1 to grade 4. Results: Chondral lesions were present in 77.4% of patients with degenerative meniscal tears and in 63% of patients with radial meniscal tears. One the other hand, osteochondral lesions were observed in only 33.9% of patients with other types of meniscal tears. 46.6% of ACL lesions accompanied by meniscal tears with longitudinal pattern, such as longitudinal tears, bucket handle tears and root tears. For the other types of meniscal tears, this percentage was 20.7. When we excluded degenerative type meniscal tears, the mean age of the patients with radial tears was 40.86±9.03 years and the mean age of the patients with other types of tear was 35.44±9.44 years. The difference was statistically significant. Conclusion: We found close relationship between osteoarthritic chondral lesions and radial tears in the root of the posterior horn of the medial meniscus. On the other side, longitudinal tears were related with ACL lesions. (The Medical Bulletin of Haseki 2014; 52: 177-80)